Strategic Model of CSR Fund Partnership for Strengthening Income Generating for Unimed as PK-BLU - Azizul Kholis; Indra Maipita; Eko Wahyu Nugrahadi; Tauada Silalahi (CERED Indonesia Institute, 2022)
This study aims to examine the potential of CSR funds for universities, especially for PK-BLU as income generating. The study was conducted from May to July 2022 by distributing questionnaires to 112 companies operating in North Sumatra Province. The test results also prove that the support of the industrial world and partnerships has an effect on the potential and CSR, while the support of universities and government regulations has no effect on the potential of CSR funds. The conclusion of this study is that stakeholders play an important role in providing pressure for companies to increase the implementation of CSR funds.